Epithelial-to-mesenchymal transition in the development of adenomyosis - Ben-Shian Huang; Hsiao-Wen Tsai; Peng-Hui Wang; Nae-Fang Twu; Ming-Shyen Yen; Yi-Jen Chen (Wolters Kluwer Medknow Publications, 2015)
Adenomyosis is a hormone-related disease that affects 10-66% of women, and women with this disorder suffer from menorrhagia, dysmenorrhea, pelvic pain, abnormal uterine bleeding, and/or infertility. Regarding the etiology of the disease, the current trend of thought is that adenomyosis or adenomyoma results as a down-growth and invagination of the endometrial basalis into the adjacent myometrium after disruption of the normally intact boundary between the two. The eutopic endometrium of adenomyosis presents invasive characteristics, including increased angiogenesis and proliferation, decreased apoptosis, induction of the local production of estrogens, induction of progesterone resistance, and impaired cytokine expression, and these changes enhance the ability of the endometrium to infiltrate the junctional zone myometrium and the growth of ectopic tissue. Hysterectomy is the major strategy to relieve secondary dysmenorrhea caused by adenomyosis. However, fertility and uterine preservation are compromised by such treatment. The traditional pharmacological therapies for adenomyosis are primarily aimed at the suppression of endogenous estrogen production, but the results are not satisfactory. Thus, there is an urgent need to develop novel treatment strategies for adenomyosis. There has been evidence that indicates that the estrogen-induced epithelial-mesenchymal transition (EMT) may play a role in the development of adenomyosis. In this article, we will concentrate on the estrogen-induced EMT in the pathogenesis of adenomyosis.